002.4 Field evaluation of standard diagnostics duo hiv and syphilis test among female sex-workers in johannesburg. (13th September 2015) - Black, V; Maseko, V; Venter, FW; Radebe, F; Mullick, S; Rees, HV; Lewis, DA
Abstract : Introduction: Point-of-care tests (POCT) for STI/HIV provide immediate results with the opportunity for same day treatment,  counselling and partner notification. Combination POCTs for HIV and syphilis are particularly beneficial for pregnant women and key populations as treating these infections early reduces vertical and community transmission. Methods: We evaluated Standard Diagnostics' Duo HIV and Syphilis Test (SD bioline) among female sex-workers (FSW) in the inner-city of Johannesburg. SD bioline was conducted on-site using whole blood according to manufacturer's instructions and compared to Genscreen HIV 1/2 V2 – 3 rd and Vironostika Ag/Ab – 4 th generation assays for HIV and to the T. pallidum particle agglutination (TPPA) test for syphilis. A Rapid Plasma Reagin (RPR) test was conducted in the laboratory to assist with classification of treponemal disease. Sensitivity, specificity, positive predictive values (PPV) and negative predictive values (NPV) were calculated Participants with HIV were referred to HIV services and those with syphilis were managed according to national guidelines. The study received ethics approval. Results: We recruited 263 FSW, 14 (5.3%) declined an HIV test and were excluded. Among the remaining 249 FSW 187 (75.1%) women were HIV positive and 51 (20.5%) had evidence of syphilis with 7 (2.8%) having active syphilis. For HIV sensitivity was 98.9% (95% CI: 95.8–99.8), specificity was 100% (95% CI: 92.7–100), PPV was 100% (95% CI: 97.5–100%) and NPV was 96.9% (95% CI: 88.2–99.5). For treponemal antibody detection, sensitivity was 66.7% (CI: 52.0–78.9), specificity was 98.0% (CI: 94.5–99.3), PPV was 89.5 (CI: 74.3–96.6) and NPV was 91.9% (CI: 87.2–95.1). Sensitivity increases to 85.7% for active syphilis (RPR > 1:4). Conclusion: Although the SD bioline performs well for HIV diagnosis, the assay has lower sensitivity for syphilis detection in our field setting compared to published laboratory evaluations. Using the test in screening programmes will detect both HIV and active syphilis but will result in overtreatment for syphilis. Disclosure of interest statement: The study was funded by USAID/PEPFAR and AIDS Fonds. SD bioline tests were provided by SD diagnostics.